2020
DOI: 10.3390/rel11110616
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Perception of Religious Education According to Religion and Gender in Spain

Abstract: The aim of our study is to verify the influence of Religious Education on Spanish adolescents by applying a quantitative study based on descriptive and social research methods which reflect the religious and social plurality of Spain, with a total of 679 secondary education students. By means of the Delphi technique, an exploratory and semi-confirmatory factor analysis, and a confirmatory analysis using structural equations, the psychometric properties of the questionnaire designed are guaranteed. Using a mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The results allow us to affirm that the students' perception about the relevance of religion (RR) by gender is not significant (t = 1.56, p = 0.423). However, other research studies have revealed gender differences, such us more positive experiences in relation to religion at school in the case of Christian women [26] and the consideration of religion as important during adolescence for Israeli Orthodox Jewish women [37].…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…The results allow us to affirm that the students' perception about the relevance of religion (RR) by gender is not significant (t = 1.56, p = 0.423). However, other research studies have revealed gender differences, such us more positive experiences in relation to religion at school in the case of Christian women [26] and the consideration of religion as important during adolescence for Israeli Orthodox Jewish women [37].…”
mentioning
confidence: 92%
“…This brief review of the scientific literature shows an interest in investigating all of those key factors that gradually shape adolescents' collective identity. One of them would be religious education in educational institutions, which has been the focus of a large number of research studies [26,27] dealing with the importance attributed by adolescents to religion in the official curriculum in the formal educational context. These studies show that they consider religion to be an important element for their life and their development as human beings, showing other ways of interrelating with peers and, even in some cases, improving their academic results [28], in addition to becoming into a facilitating or limiting factor in the process of social inclusion [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation